Cardiac Magnetic Resonance Imaging of the Myocardium in Chronic Kidney Disease - Eva Kis; Laszlo Ablonczy; György S. Reusz (Karger Publishers, 2018)
Early stages of chronic kidney disease (CKD) are often underdiagnosed, while their deleterious effects on the cardiovascular (CV) system are already at work. Thus, the assessment of early CV damage is of crucial importance in preventing major CV events. Myocardial fibrosis is one of the major consequences of progressive CKD, as it may lead to reentry arrhythmias and long-term myocardial dysfunction predisposing to sudden death and/or congestive heart failure. Subclinical myocardial fibrosis, with a potential key role in the development of uraemic cardiac disease, can be measured and characterised by appropriate cardiac magnetic resonance (CMR) techniques. Fibrosis detection was initially based on the contrast agent gadolinium, due to the superiority in sensitivity and accuracy of contrast-based methods in fibrosis assessment relative to native techniques. However, the severe consequences of gadolinium administration in uraemia (nephrogenic systemic fibrosis) have forced practitioners to re-evaluate the methodology. In the present overview, we review the possible contrast-based and contrast agent-free CMR techniques, including native T1 relaxation time, extracellular volume and global longitudinal strain measurement. The review also summarises their potential clinical relevance in CKD patients based on recently published studies.